Early Detection of Infectious Diseases among the Refugees of UNHCR in South Tangerang, Banten; the Problems and Strategies to Prevent the Disease's Transmission - Nasution, Silvia Fitrina; Nisa, Hoirun (Indonesian Journal of Tropical and Infectious Disease, 2024)
The previous study at Puskesmas Pisangan, Ciputat had reported that among 23.8 % patient of the UNHCR was infected by malaria Plasmodium vivax, and one patient with bacterial urinary infection. However, the result can not represent the actual case of the disease, because of the lack number of participant to visit the Puskesmas since the Covid-19 pandemic which had been contributing to decrease number of the patients. The study purposed to improve data and information about parasitic infection, and to design strategy in early detection and prevention to the disease. Design of the study was approached in cross-sectional with a total sampling method of the UNHCR out patients visiting the Puskesmas Pisangan and Cirendeu.We collected specimen of feces, urine, and blood, and performed blood diff-count, rapid diagnostic, microscopic, dipstick, and bacterial culture. The study revealed some parasitic and bacterial infections as defined: five cases (17.24%) of malaria, which is suspected as imported cases; Enterobacteriacea family as non-specific bacteria of negative gram in urine; also Entamoeba coli in stool. This finding was confirmed 17.24% of leucocytosis in blood diffcount and 24.14 % in urinalysis. By nationality, Sudanese was detected the most prevalent 10.34% of parasitic infections, followed by Somalia (6.9%), Yaman (3.45%), and Afghanistan (3.45%) respectively. While mosquitoes and poor living conditions were also contributed as the major potential risk of transmission to the diseases. In conclusion, early detection, health screening, vaccination, access to primary, and upgraded levels of healthcare are important for diseases control and management to prevent transmission.